Princípios jurídicos e regulação - Lopes, Othon de Azevedo (2011)
1) Reasons: The roots of independent authorities and regulation in the regulatory state lie within the influence of the contemporary productivism on law, as it brought forth a precise knowledge that displaced a more fluid and approximate one. The techno-bureaucratic structure of the regulatory authorities does not guarantee, though, the legitimacy of their decisions. Their independence and neutrality pay tribute mainly to the economic system dynamics, which aims at assuring property and contract rights in a given sector. Those rights are necessary for the political bureaucratic system to render public interest utilities in a more effective way. The new set of demands from the economic system led to crescent rule-making power in the Executive branch due to the inability of the classical deliberative legislative process to deal with issues that depends upon rapid and specialized decisions. Systemic demands have been absorbed by the law, resulting in a new framework that created new structures of rule-making process to face the needs of a society increasingly specialized and a state that carries on a strong compensatory mission. In spite of that, the risks and potential coercion involved in regulation point out to the danger of attributing to the Executive branch an amorphous and curbless power. 2) Aims: it is imperative to limit the regulatory institutional endowments that encompass three dimensions: limits, conformations, guidelines and legitimation. 3) Theoretical aspect: due to the specific services and goods demanded, and the technical characteristics of the issues involved, from the point of the filosophical hermeneutics, the regulation makes use of a specialized and unambiguous language. Principles have their roots in the natural language, which opens up a world of experiences not possible to be translated into formulas and able to create a more complex social relation that surpasses a consumer-oriented social role. It is a distinctive sign of the regulation to overestimate the economic and technical aspects. 4) Hipothesis: legal principles go beyond the rigidity of the mathematical-based systems of knowledge, and bring unity to the rationale of social consensus through the use of natural language. From the perspective of principles, it is possible to curb the technicism and bureaucratic excesses of the plethora of rules in each sector regulated by agencies, opening up a space of legitimacy and allowing for a unified perception of the regulatory phenomenon. 5) Conclusive synthesis: principles turn the mathematical rationale dependent on precise concepts into a reflexive rationale fulfilled through adjudications. Principles underpin and legitimate the law by transforming a technical-scientific knowledge into a prudential and philosophical knowledge. On the other hand, a legal logical system makes the structural coupling between law, economics and political power possible, as it conveys recognizable messages that influence specific codes of an agency regulated by political power, and a market regulated by money. The relation between principles and regulation thus conceived makes the translation of mundane expectations into specialized and systemic social spheres possible